Mobile communication and low-skilled migrants' acculturation to cosmopolitan Singapore - Aricat, Rajiv George; Ling, Richard Seyler (Lexington Books, 2018)
"A socially situated exploration of South Asian migrants in Singapore that critically examines migrants' negotiations of cultural identity, power, and friendship networks in mediated mobile phone spaces"--